Absorption Efficiency Assessment and Uncertainty Measurement of the Sodium Arsenite Method for Ambient NO2 Determination - Rishu Agarwal; Shankar G. Aggarwal (Aerosol and Air Quality Research)
Abstract The absorption efficiency and uncertainty involved in the sodium arsenite method (modified Jacobs and Hochheiser method) of NO2 measurement were studied using two standard gas concentrations (4.86 ± 0.10 µmol mol−1 (ppm) and 1.95 ± 0.10 µmol mol−1 (ppm)). An average of 71 ± 3% and 71 ± 6% absorption efficiencies, respectively were observed against reported efficiency of 82% in the published standard (IS 5182 (Part 6): 2006, BIS, 2006a) in 1-impinger system at sampling flow rate of 1 L min−1 and absorbing solution temperature of 10–15°C during gas absorption in impinger. The difference is accounted for by the variation in flow rate used in present study (1 L min−1) and that in standard method (0.2 L min−1). Uncertainty involved in the method was calculated considering a range of factors directly or indirectly affecting the measurement and was found to be 15%. Based on the comparison study performed for NO2 ambient measurements using an equivalent method (chemiluminescence continuous method) and 1-impinger system reference method, the present study highlights the importance of accurate determination of absorption efficiency factor in the NO2 pollutant measurement at laboratory level. Variations observed in the absorption efficiency and the data from inter-comparison study between manual and real-time method warranted this study to be taken up to provide solutions for improvement of the method. The use of at least three absorbers/impingers (connected in series) instead of one to obtain absorption efficiency close to unity is proposed to make the reference method independent from the use of absorption efficiency factor thus ensuring the improved data quality and comparability.